Characteristics of an Internal Dielectric Barrier Discharge Plasma-induced Blowing Device - Y. Zhang; B. Dong; D. Yang; X. Yan; Y. Li (Journal of Applied Fluid Mechanics)
This paper investigates the blowing characteristics of internal dielectric barrier discharge (IDBD) plasma actuators and their application in the flow control field. The effects of different internal channel parameters and the number of actuators on the performance of the IDBD plasma exciter are evaluated using PIV experiments. The results show that the internal actuators are effective in generating blowing with a certain kinetic energy at the outlet, with a velocity of up to 1.5 m/s. The blowing characteristics are significantly affected by the channel height (H) and outlet length (L). Deflection of the channel inlet or outlet introduces more possibilities for the installation of IDBD plasma actuators, albeit with a loss of about 15% of the kinetic energy of the blowing. With a modulated wave setup, the plasma actuator allows for unsteady blowing and generates frequency-controllable vortices, providing new possibilities for active control of frequency-specific wake streams. In addition, the flow control performance of the IDBD plasma actuator is demonstrated in the wake of a plate with a blunt trailing edge (TE), confirming the actuator's ability to alter the flow pattern and reduce the characteristic frequency. Despite the limitations of actuators in energy efficiency, the IDBD plasma actuator still shows great potential for flow control while increasing resistance to environmental effects.